Design and analysis of cascade liquefaction processes for coproducing liquid ethane and LNG. (16th March 2022) - He, Ting; Lin, Wensheng; Du, Zhimin
Summary: Ethane recovery is an important way to increase the economic benefits of unconventional natural gas, such as shale gas. However, current researches did not focus on obtaining high purity and high recovery rate of ethane. In this study, two pure refrigerant cascade natural gas liquefaction processes without (Process 1) or with (Process 2) flash gas recovery are proposed to coproduce high‐purity liquefied ethane gas (LEG) and liquefied natural gas (LNG). The proposed processes are combined with advanced distillation methods to reduce the energy consumption through process and energy integration. Aspen HYSYS V11 and genetic algorithm (GA) are used to simulate proposed processes and optimize the refrigeration cycles, respectively. To search the optimal conditions of distillation column, power consumption under different distillation pressure is comparatively analyzed, and the optimal distillation pressure is about 2.7 MPa. According to the optimization results, the specific power consumption of Process 1 is 0.4384 0.4584 kWh/Nm 3 (NG), and that of Process 2 is 0.4336 0.4503 kWh/Nm 3 (NG) when ethane content is 10% 40%. Process 2 is preferred for lower power consumption and no material waste. Further study is conducted to research the effect of throttling temperature and ethane content on the system performance of Process 2. In addition, the feasibility exploration of cryogenic compression shows that re‐compression of natural gas after distillation is not energy saving for the proposed process. Abstract : Novel cascade natural gas liquefaction processes with or without flash gas recovery are proposed to coproduce high‐purity ethane and LNG. The influence of distillation pressure on the specific power consumption of the system is analyzed to search the optimal conditions of distillation column. According to the optimization results of the genetic algorithm, the process with flash gas recovery is preferable in energy consumption and material waste aspect, with a specific power consumption of 0.4336 0.4503 kWh/Nm 3 (NG) when ethane content is 10% 40%.